Involvement of Indoleamine 2, 3-Dioxygenase in Impairing Tumor-Infiltrating CD8+ T-Cell Functions in Esophageal Squamous Cell Carcinoma. (13th October 2011) - Zhang, Ge; Liu, Wan-Li; Zhang, Lin; Wang, Jun-Ye; Kuang, Miao-Huan; Liu, Peng; Lin, Yue-Hao; Dai, Shu-Qin; Du, Jun
Abstract : The indoleamine 2, 3-dioxygenase-(IDO-) mediated microenvironment plays an important role in tumor immune escape. However, the inhibitory effects of IDO on the CD8 + tumour-infiltrating lymphocytes (CD8 + TILs) in esophageal squamous cell carcinoma (ESCC) have not been clarified yet. Here, we found that the level of IDO expression in ESCC tumor specimens correlated with a reduction in the number of CD8 + TILs. Patients with high IDO expression and a low number of CD8 + TILs had significantly impaired overall survival time. IDO expression and functional enzyme activity in ESCC cell lines could be induced by IFN γ . When exposed to the milieu generated by IDO-expressing Eca109 cells, the CD8 + TILs were suppressed in proliferation, and their cytolytic functions against target tumor cells were lost. These results suggested that impairing CD8 + TIL functions by IDO expressed in ESCC possibly contributed to the finding that patients with higher IDO expression have more aggressive disease progression and shorter overall survival time.